CLINICAL STUDY OF CEFTRIAXONE (Ro 13-9904) - OSONOI, TAKESHI; TAKAHASHI, KIYOHITO; SAGARA, MORIO; TAKEBE, KAZUO; KURIHARA, AIICHIRO; KUMASAKA, YOSHIHIRO; WATANABE, HAJIME; TAMURA, TOYOKAZU; NAKAHATA, HISASHI; MASAKI, NAOYOSHI; YASHIRO, HITOSHI; MAKINO, ISAO; et al. (CHEMOTHERAPY, 1984)
Ceftriaxone (CTRX, Ro 13-9904) was studied about its clinical efficacy, side effects and laboratory values with 20 cases of infectious diseases: 10 cases with pneumonia, 1 with acute bronchitis, 2 with acute cystitis, 2 with chronic cystitis, 2 with acute pyelonephritis, 2 with chronic pyelonephritis and 1 with chronic cholangitis. 16 cases received CTRX as an one-hour drip injection and the other 4 as an intravenous injection. 4 cases were treated with 1 g dose once a day, 14 cases with 1 g twice a day and the remaining 2 with 0.5 g twice a day. The duration of treatment ranged from 5 to 15 days. As the pathogen, S. aureus and S. pn. were identified each in one case of pneumonia. S. pn. was detected also in a case of acute bronchitis. In urinary tract infections, monoinfections were found to occur due to E. coli in 2 cases, due to C. freundii, P. cepacia and P. maltophilia each in one case, and 3 cases had mixed infections due to E. coli associated with γ-Strep. sp., P. aeruginosa associated with S. faecalis and E. coli associated with Aeromonas hydrophilia, respectively. The cases studied showed the following clinical efficacy: 10 cases of pneumonia; 1 excellent, 8 good, 1 fair. 1 case of bronchitis; good. 2 cases of acute cystitis and 2 of chronic cystitis; 2 excellent, 2 good. 2 cases of acute pyelonephritis; 1 good, 1 poor. 2 cases of chronic pyelonephritis; 1 excellent, 1 good. 1 case of chronic cholangitis; good. As a whole, excellent responses were observed in 4 cases, good in 14, fair in 1 and poor in 1, and the efficacy rate was 90%. As to side effects, 37.8°C of fever appeared 13 days after administration in one case, but it recovered by discontinuation of treatment. The laboratory test recognized eosinophilia (1380) 10 days after administration of this drug and observed a slight elevation of S-GOT in one case.